Protective Effect of Buckwheat Polyphenols Against Long-Lasting Impairment of Spatial Memory Associated With Hippocampal Neuronal Damage in Rats Subjected to Repeated Cerebral Ischemia - Fengling Pu; Kenichi Mishima; Nobuaki Egashira; Katsunori Iwasaki; Tomohiro Kaneko; Tomoko Uchida; Keiichi Irie; Daisuke Ishibashi; Hajime Fujii; Kenichi Kosuna; Michihiro Fujiwara (Elsevier, 2004)
In the present experiment, we studied the action of buckwheat polyphenol (BWP, from Fagopyrum esculentum MOENCH) in a repeated cerebral ischemia model, which induced a strong and long-lasting impairment of spatial memory in 8-arm radial maze with hippocampal CA1 cell death in rats. BWP (600 mg/kg, continuous 21-day p.o.) significantly ameliorated not only the impairment of spatial memory in the 8-arm radial maze, but also necrosis and TUNEL-positive cells in the hippocampal CA1 area subjected to repeated cerebral ischemia (10 min × 2 times occlusion, 1-h interval) in rats. In order to investigate the mechanism of BWP protective action, we measured the release of glutamate and NOx- (NO2- +NO3-) production induced by repeated cerebral ischemia in the rat dorsal hippocampus using microdialysis. A 14-day BWP treatment significantly inhibited the excess release of glutamate after the second occlusion. In addition, the BWP remarkably suppressed a delayed increase in NOx- (NO2- +NO3-) induced by repeated cerebral ischemia in the dorsal hippocampus as determined in vivo by microdialysis. However, the 14-day treatment did not affect hippocampal blood flow in either intact rats or rats subjected to repeated ischemia measured by lasser Doppler flowmeter. These results suggested that BWP might ameliorate spatial memory impairment by inhibiting glutamate release and the delayed generation of NOx- in rats subjected to repeated cerebral ischemia. Keywords:: buckwheat polyphenol, repeated cerebral ischemia, spatial memory, glutamate, nitric oxide